IMPLEMENTASI ICE BREAKING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V MI MIFTAHUL HUDA BABAKAN TENGAH - Nurmatin, Suci (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI, 2023)
One of the creativity in implementing learning strategies is applying ice breaking, the implementation of ice breaking can be interpreted as the implementation of activities carried out to dilute the learning atmosphere aimed at eliminating boredom in the classroom, therefore the teacher must be able to increase learning motivation so that learning can be effective. This study aims to find out how to implement ice breaking in increasing the learning motivation of fifth grade students at MI Miftahul Huda Babakan Tengah. This study uses a descriptive qualitative approach, the source documentation. The final result of this research is the implementation of ice breaking in class V combined with the material being delivered such as making song lyrics, quizzes of data obtained through observation, interviews, questionnaires and. The type of implementation of ice breaking in class V is different from the application in lower classes, including quizzes, songs, games. For this type of ice breaking, clapping is occasionally used. With the implementation of ice breaking students are motivated in learning, this can be seen from the increased enthusiasm for student learning, the growth of interaction in learning, learning does not feel bored. Teachers often give rewards in the form of prizes and praise, the fifth grade teacher also makes works in the form of gelis trees that are pasted in the classroom containing the names of students who have received rewards from student learning outcomes.